Development of Android-Based Media for Teaching Islamic Religious Education and Character Development Through Appreciation of the Books of Allah - Munib, Achmad; Ghoni, Aris Abdul; Mustagfirin, Mustagfirin; Rois, Nur (Universitas Negeri Semarang, 2024)
A communication tool and information source in education, including the utilization of learning media, necessitates careful consideration from teachers in selecting appropriate media to enhance student motivation in learning, aiming for benefits such as: 1) enhancing the appeal of the educational process, 2) optimizing efficiency and effectiveness in learning, and 3) conserving energy and time. In the realm of Islamic Religious Education and Character lessons, particularly focusing on the concept of Believing in Allah's Books, students commonly encounter challenges in grasping this knowledge. The difficulties faced by students in comprehending Islamic Religious Education and Character lessons concerning Believing in Allah's Books stem from various factors, as revealed through surveys and observations conducted at SMPN 2 Dempet Demak. Among these challenges is the struggle to grasp the core essence of the material as presented in textbooks and slide presentations. Additionally, the conventional teaching approach employed by educators contributes significantly to diminishing students' enthusiasm and motivation for learning. The evolving landscape of media usage presents a challenge for teachers in fulfilling their roles effectively to meet educational objectives. The widespread availability and accessibility of smartphones as a learning tool can profoundly impact students' learning experiences. Apart from being relatively novel facilities, students are more inclined to engage with tools that are current and resonate with their everyday experiences.